Academic Administration Based on the Four Brahmavihāra Principles by Educational Institution Administrators under the Khon Kaen Primary Educational Service Area Office 1 - Tanonthong, Pongsathon; Saikham, Sunthon; Chanthasombat, Chalard (Journal of Buddhist Education and Research (JBER), 2025)
This research aimed to: 1) study academic administration based on the principles of the Four Brahmavihāra of educational institution administrators in a group of the office of Khon Kaen primary educational service area office 1; 2) propose guidelines for developing academic administration based on the Four Brahmavihāra principles of educational institution administrators in a group of the office of Khon Kaen primary educational service area office 1. A mixed-methods research design was employed. For the quantitative component, a questionnaire with a reliability coefficient of 0.99 was used. The sample consisted of 304 participants, including school principals and teachers. The statistical methods used included frequency, percentage, mean, and standard deviation. For the qualitative component, data were collected through interviews with 12 key informants, who were selected using purposive sampling. The data were analyzed using content analysis and presented in descriptive form. The research results were as follows: 1. Overall, academic administration based on the Four Brahmavihāra was found to be at the highest level. The aspect with the highest mean score was administration based on Metta (loving-kindness), while the aspect with the lowest mean score was administration based on Upekkhā (equanimity). 2. The proposed guidelines for academic administration based on the Four Brahmavihāra indicate that, in managing school curriculum development, learning process enhancement, assessment and evaluation, credit transfer, the development and use of educational technology, and academic supervision, administrators should establish a clear vision and goals, plan administrative activities effectively, show care and support equally, and promote good interpersonal relationships among teachers. Furthermore, they should foster learning communities to enhance the school’s academic excellence.